Kedudukan Peradilan Administrasi Negara Sebagai Upaya Dalam Mendorong Terbentuknya Pemerintahan Yang Baik - Khalid Dahlan; Anna Erliyana Chandra (Jurnal Justisia : Jurnal Ilmu Hukum, Perundang-undangan dan Pranata Sosial, 2021)
Efforts to encourage the implementation of proper governments are continually done in each country, including one of them in the Republic of Indonesia. A decent government can be realized if it is followed by government decisions that are responsive to the needs and interests of the community. The decision of the state administration officials in the effort to realize a proper government must be based on the general principles of good governance, especially those that have been mentioned in Act. No. 30 of 2014 concerning Government Administration. In term of realizing a proper government, it not only becomes the duty of the state administration officials through the decisions formed, but also the involvement of the community as the plaintiff for any government decision that feels disadvantaged and the state administrative court as an institution that examines and decides disputes between the community and the government by continuing to refer the laws and general principles of a good government is part of realizing a good governance.